Search for excited leptons in proton-proton collisions at root s=7 TeV with the ATLAS detector - Onofre, A. (2012)
The ATLAS detector is used to search for excited leptons in the electromagnetic radiative decay channel ℓ∗→ℓγ. Results are presented based on the analysis of pp collisions at a center-of-mass energy of 7 TeV corresponding to an integrated luminosity of 2.05  fb−1. No evidence for excited leptons is found, and limits are set on the compositeness scale Λ as a function of the excited lepton mass mℓ∗. In the special case where Λ=mℓ∗, excited electron and muon masses below 1.87 TeV and 1.75 TeV are excluded at 95% C.L., respectively.